Upper transversal hepatectomy for pediatric liver tumors based on the inferior right hepatic vein - Mufaddal Khuzema Kazi; Sajid Shafique Qureshi (Wolters Kluwer Medknow Publications, 2021)
Introduction: Tumors located at the hepatocaval junction with the involvement of hepatic veins conventionally warrant major liver resections. Appreciation of sizeable inferior right hepatic vein can allow preservation of uninvolved inferior segments of the liver. Operative Technique: Preoperative and intraoperative identification of sizeable inferior right hepatic and other accessory or communicating veins in combination of intra-operative ultrasound guidance for resection to preserve inferior segments of the liver with adequate venous drainage. Application of upper transversal resections for pediatric liver tumors at the hepatocaval confluence was illustrated with description of operative technique and patient selection. Conclusions: Parenchymal preserving surgeries are possible for pediatric liver tumors located at the hepatocaval confluence by identification of accessory draining veins to the inferior segments. This along with meticulous parenchymal dissection with ultrasound guidance to preserve all uninvolved veins is key to safe upper transversal resections.